Analisis Strategi Rantai Pasok (Supply Chain) Selada Di CV Tirta Fertindo Pratama Semarang: Supply Chain Strategy Analysis Of Lettuce In CV Tirta Fertindo Pratama Semarang - Khairul Ashari Nasution (Universitas Widya Gama Mahakam, 2021)
Supply chain is a way that provides information system support to management in terms of procurement of goods as well as managing networks among partners to maintain the level of product availability required by consumers. This research was aimed to analyze supply chain strategies and formulate the best strategy for the supply chain of lettuce CV. Tirta Fertindo Pratama. The research method used is case study. Respondents used in this study are manager, 5 employees, 3 wholesalers and 5 consumers selected by snowball sampling. Research methods used in this research is Internal Factor Evaluation (IFE) matrix, External Factor Evaluation (EFE) matrix, Internal-External (IE) matrix, SWOT matrix, and Quantitative Strategic Planing Matrix (QSPM). The result showed that supply chain activities consist three chains namely companies, wholesalers dan consumers. IFE matrix analysis shows that the greatest strength possessed by the company is location that close to the market with score 0.502 and the greatest weakness is poor business management with score 0.274. EFE matrix analysis shows that the biggest opportunity of the company is low and stable price with score 0.471 and the biggest threats is a high level of competition with score 0.218. IE matrix analysis shows that the company is in cell IV which means the company is in a position to grow and build. QSP matrix analysis shows that priority strategy of the company is to penetrate the market.